Analysis of the unemployment gender gap in Colombia 2001-2021: A SARIMA-GARCH model approach - Romero Mantilla, Carolina; Cárdenas, Greissly; Ramoni-Perazzi, Josefa (Cuadernos de Administración, 2022)
Reducing the unemployment gender gap is seen as an indicator of women’s empowerment capacity for the equitable growth of the country’s economy. At the regional level, Colombia exhibits one of the highest unemployment gaps, despite the efforts made to close them. The objective of this study is to model the evolution of the unemployment gender gap in Colombia during the period 2001:01 to 2021:06, to forecast its behavior, and determine its volatility. For this purpose, a Seasonal Autoregressive Integrated Moving Averages (SARIMA) and Generalized AutoRegressive Conditional Heteroskedasticity model (GARCH) were fitted. The results indicate that, although the gender gap had been slightly declining in the last two decades, it was adversely affected by the Covid-19 pandemic, causing the gap to increase again. On the other hand, there is an increase in the volatility of the series, making it more vulnerable to economic and seasonal cycles. Finally, it is forecast that the gap will tend to decrease in the following months, however, it will increase again in December due to the seasonal component.